The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/0004563212473450
|View full text |Cite
|
Sign up to set email alerts
|

Higher circulating bile acid concentrations in obese patients with type 2 diabetes

Abstract: Background: Bile acids (BAs) play an important role in releasing incretin hormones via the enteroendocrine L-cell surface TGR5 receptors. The aim of this study was to investigate the difference in BA concentration at baseline and in response to a meal stimulus between type 2 diabetes mellitus (T2DM) and a matched normoglycaemic group. Materials and methods: A cross-sectional study of 12 patients with known T2DM and 12 matched normoglycaemic controls compared BA fractions after an overnight fast and following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 20 publications
4
53
0
Order By: Relevance
“…14,38 T2DM is associated with altered BA metabolism. 9,25,39,40 Total BAs in obese persons with T2DM are reported to be higher compared with normoglycemic obese controls during fasting and postprandially; 9,39,40 some studies showed that this was driven by an increase in either glycine and/or taurine-conjugated BAs. 39,40 Another study showed that plasma CA and CDCA were inversely associated with insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…14,38 T2DM is associated with altered BA metabolism. 9,25,39,40 Total BAs in obese persons with T2DM are reported to be higher compared with normoglycemic obese controls during fasting and postprandially; 9,39,40 some studies showed that this was driven by an increase in either glycine and/or taurine-conjugated BAs. 39,40 Another study showed that plasma CA and CDCA were inversely associated with insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, postprandial hyperglycemia -an early defect seen in impaired glucose tolerance (IGT) and T2D -is a major contributor to HbA1c and even recognized as an independent risk factor for cardiovascular disease (18,19); a link that may also prove important considering the emerging evidence suggesting a role of bile acids in cardioprotection (20). Substantial rearrangements of bile acid metabolism in T2D patients are well established, including changes in pool size, pool composition, synthesis rate and postprandial plasma concentrations (21)(22)(23)(24)(25)(26)(27). We show that postprandial concentrations of secondary bile acids were higher in T2D patients vs. NGT.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study may not generalize to patients outside the BMI and age restriction in our study, and probably of more importance, to patients with type 2 diabetes or severe metabolic disease. Previous studies have shown different bile acid profiles and responses in subjects with type 2 diabetes compared to non-diabetic subjects both before and after bariatric surgery [11,45].…”
Section: Discussionmentioning
confidence: 99%